Optimización en los procesos de recepción y comercialización de maíz en la empresa comercial “don pancho” del cantón El Empalme, año 2013 - Solis Intriago, Elio Fernando (2015)
Most of the production of corn is yellow grain goes to feed consumption. Its use for the manufacture of fructose, oils and fuels has grown rapidly in recent years, a small part of its production is white grain is intended mostly flour for human consumption. Today in the village of El Empalme there are 12 commercial houses dedicated as a center for collection and marketing of agricultural products of which three or four are with all the infrastructure for grain cleaning process. The main objective of this research was based on efficient portfolio management, monitoring parame trizando and conveniently critical aspects of the process, not to mention the team involved. Mechanisms were established to monitor the results of the activities and processes, excess processing time, eliminate confusion in a department or an operation that allows increasing the level of customer satisfaction. Flow diagrams were developed cleaning and drying corn recital 25 and 26 degrees dispatched by quintals in bags with a current time of 740.4 seconds, and with the same degree 728.30 seconds shipped in bulk, and the amount of the plant layout based on the flow chart, identifying each of the areas, the standard time will be determined in the cleaning and drying considering an assignment criterion tolerance of 20%, with a time compensation of 5% of the time Basic. According to the results the time should be granted to workers for concessions fatigue throughout the working day is equal to 73 minutes with an effective working time of 460 minutes, this allows to efficiently manage resources and achieve management Quality, accepting the hypothesis.